Placode and neural crest origins of congenital deafness in mouse models of Waardenburg-Shah syndrome - Jaime Tan; Alicia Duron; Henry M. Sucov; Takako Makita (iScience, 2025)
Summary: Mutations in the human genes encoding the endothelin ligand-receptor pair EDN3 and EDNRB cause Waardenburg-Shah syndrome (WS4), which includes congenital hearing impairment. The current explanation for auditory dysfunction is defective migration of neural crest-derived melanocytes to the inner ear. We explored the role of endothelin signaling in auditory development in mice using neural crest-specific and placode-specific Ednrb mutation plus related genetic resources. On an outbred strain background, we find a normal representation of melanocytes in hearing-impaired mutant mice. Instead, our results in neural crest-specific Ednrb mutants implicate a previously unrecognized role for glial support of synapse assembly between auditory neurons and cochlear hair cells. Placode-specific Ednrb mutation also caused impaired hearing, resulting from deficient synaptic transmission. Our observations demonstrate the significant influence of genetic modifiers in auditory development, and invoke independent and separable roles for endothelin signaling in the neural crest and placode lineages to create a functional auditory circuitry.